Produção escrita e contextualização: reflexões sobre propostas de redação para o Ensino Médio - Lima, Salete de Almeida Moraes (2011)
This dissertation is inserted in the line of research Reading Writing and Teaching of Portuguese, and its main purpose is a study on the context and written production in high school. Are the specific goals: to raise background data production activities in writing textbooks, to analyze whether or not there is adequacy of contextual point of view, the activities proposed. The corpus is formed by a set of exercises productions of texts from Textbook currently used in the Public Schools State. The procedure adopted in the work is theoretical, analytical and theoretical foundation lies in the field of studies on the text in the speech. Given the limits found in the proposals examined, it is proposed a retextualization written for production activities guided by contextual elements